2013
DOI: 10.4304/tpls.3.2.363-370
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis and Second Language Writing

Abstract: The purpose of the study is to compare and examine types of written errors by EFL and ESL learners at under graduate level in English Language and suggest remedial measures to overcome the committing of errors. The data for the study were 200 students in the age range of 20 to24 at under graduate level in Mysore, India as ESL learners and Bushehr, Iran as EFL learners participated in this study. The results of the study indicate that the total number of errors committed by the Iranian students was 3045 and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 6 publications
5
19
2
Order By: Relevance
“…This finding is slightly different from Khansir's (2013) research finding on Indian and Iranian undergraduate students showing that the maximum errors committed by research subjects were punctuation while the minimum errors were spelling.…”
Section: ) My Mother Likes Watching Korean Drama But I Like Indonesicontrasting
confidence: 56%
See 1 more Smart Citation
“…This finding is slightly different from Khansir's (2013) research finding on Indian and Iranian undergraduate students showing that the maximum errors committed by research subjects were punctuation while the minimum errors were spelling.…”
Section: ) My Mother Likes Watching Korean Drama But I Like Indonesicontrasting
confidence: 56%
“…So, college teachers should not overlook grammar teaching while they are teaching writing. Khansir (2013) exploring errors made by Iranian and Indian undergraduate students found out that the maximum errors committed by the research participants were punctuation. And the minimum errors made by the students were spelling.…”
Section: Introductionmentioning
confidence: 99%
“…This stems from the fact that it is considered as an analytical tool that learners use in order to learn (Khansir, 2013). The outcome of error based analysis of students' essays therefore serves as an effective means of improving the language of students as it gives them an insight into some errors that they usually make in their writing.…”
Section: Review Of Pioneering Studies On Error Analysismentioning
confidence: 99%
“…The study also had as an additional aim of providing remedy to curb the situation by outlining and recommending measures that can be adopted to curb those errors that were identified in the students' written texts. By making use of 200 non-native speakers of English students from two main geographical settings (Indian & Iran) at the undergraduate levels, Khansir (2013) posited that the Iranian students committed 3,045 errors in their writing while their Indian counterparts had 3,274 errors. Khansir (2013) further confirmed that "punctuation" errors dominated the errors that were identified in the essays of students from the two different cultures.…”
Section: Review Of Pioneering Studies On Error Analysismentioning
confidence: 99%
“…The analysis on errors made by ESL learners can be seen in the study of Khansir (2013). He compared and examined the error types found in the written products of ESL and EFL students.…”
Section: Previous Studiesmentioning
confidence: 99%